Faecal microbiota transplantation—the Austrian approach. (November 2014) - Kump, P. K.; Krause, R.; Allerberger, F.; Högenauer, C.
Abstract The intestinal microbiome is essential for maintaining human health and defending against intestinal pathogens. Alterations of the intestinal microbiota, also termed dysbiosis, play a pivotal role in the pathogenesis of various human diseases. Faecal microbiota transplantation (FMT) is aimed at correcting these alterations by delivering faecal microorganisms from a healthy person to the intestines of a patient. At present, recurrent Clostridium difficile infection is the only indication supported by solid scientific evidence, but many ongoing studies are investigating FMT in other dysbiosis‐related diseases, such as inflammatory bowel disease. As there are no systematic methodological investigations, several questions about techniques, donor screening and safety issues remain. This shortage of evidence, especially on long‐term safety concerns, is leading to worldwide controversy regarding the use of FMT. Regulations by healthcare authorities vary among different countries. This review reflects the Austrian situation and its FMT guidelines concerning indications, techniques and donor screening, recently developed by local scientific societies.